Chronic IL-15 Stimulation and Impaired mTOR Signaling and Metabolism in Natural Killer Cells During Acute Myeloid Leukemia - Bou-Tayeh, Berna; Laletin, Vladimir; Salem, Nassim; Just-Landi, Sylvaine; Fares, Joanna; Leblanc, Raphael; Balzano, Marielle; Kerdiles, Yann M.; Bidaut, Ghislain; Hérault, Olivier; Olive, Daniel; Aurrand-Lions, Michel; et al. (Frontiers in Immunology, 2021)
Natural Killer (NK) cells are potent anti-leukemic immune effectors. However, they display multiple defects in acute myeloid leukemia (AML) patients leading to reduced anti-tumor potential. Our limited understanding of the mechanisms underlying these defects hampers the development of strategies to restore NK cell potential. Here, we have used a mouse model of AML to gain insight into these mechanisms. We found that leukemia progression resulted in NK cell maturation defects and functional alterations. Next, we assessed NK cell cytokine signaling governing their behavior. We showed that NK cells from leukemic mice exhibit constitutive IL-15/mTOR signaling and type I IFN signaling. However, these cells failed to respond to IL-15 stimulation as illustrated by reduced activation of the mTOR pathway. Moreover, mTOR-mediated metabolic responses were reduced in NK cells from AML-bearing mice. Noteworthy, the reduction of mTOR-mediated activation of NK cells during AML development partially rescued NK cell metabolic and functional defects. Altogether, our data strongly suggest that NK cells from leukemic mice are metabolically and functionally exhausted as a result of a chronic cytokine activation, at least partially mediated by IL-15/mTOR... NK cells from AML patients also displayed reduced CD122 expression and showed cuesof reduced metabolic response to IL-15 stimulation in vitro, suggesting that a similar mechanism might occur in AML patients. Our study pinpoints the dysregulation of cytokine stimulation pathways as a new mechanism leading to NK cell defects in AML.